Early-life undernutrition in the great Chinese famine and the risk of early natural menopause: a retrospective cohort study in Western China - Xu, Xiaoyang; Zhang, Yong; Qi, Xiaoya (Frontiers in Nutrition, 2024)
Purpose: Early age of menopause may increase the risk of fracture, cardiovascular diseases, and all-cause mortality. The aim of this study is to investigate the relation between early life undernutrition in the Great Chinese Famine and risk of early natural menopause.Methods: A famine exposure retrospective cohort was established during 2017-2018. Postmenopausal women who was born during 10/01/1956-09/30/1964 and came to the hospital for routine health examinations were candidates for studying. Famine time was defined from January 1, 1959 to December 31, 1961. Three type of early life famine exposure status was determined by the participant's date of birth. Natural menopause age below 45 was defined as early menopause. The association between early life famine exposure status and the risk of early natural menopause was confirmed by multiple logistic regression.Result: A total of 3,337 participants born around famine were included in this study. The prevalence of early menopause was 13.1%, 10.0%, and 8.3% for those born before, during, and after the famine, respectively. The multiple logistic regression showed that women born before famine significant increase the risk of early menopause compared to nonexposure (born after famine) (the fully adjusted OR=1.463, 95%CI=1.049-2.042). The fetal famine exposure did not significantly increase the risk of early menopause (the fully adjusted OR=1.244, 95%CI=0.878-1.764).Long-term early childhood famine exposure which caused chronic undernutrition at their young ages increased the risk of early menopause. Early life time undernutrition can be recognized as an adverse factor of female reproductive development and aging. This cohort study further confirmed the hypothesis of developmental origins of healthy and disease from the aspect of women's reproductive health. Further mechanism study is warranted.